2020
DOI: 10.35333/jrp.2020.226
|View full text |Cite
|
Sign up to set email alerts
|

Experimental design approach for development of cocrystals and immediate release cocrystal tablet of atorvastatin calcium for enhancement of solubility and dissolution

Abstract: The objective of the present work was to prepare cocrystals of poorly soluble drug Atorvastatin Calcium (AVA) with the aim of increasing its solubility and dissolution properties. Screening of 8 cocrystal formers (CCFs) was performed by Hansen solubility parameter (HSPs) using 4 methods-neat grinding, solvent drop grinding, solvent evaporation and sonocrystallization in equimolar ratio. Solubility of AVA cocrystal (1.9 fold increase) in comparison to plain AVA drug has been demonstrated with solubility experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Additionally, these agglomerate particles still existed after 10 h, and it can be inferred that this part of ATC will not be absorbed by the body, thus causing the loss of the API. Surprisingly, this dissolution rate of the ATC crystals of the most uniform form I was also the fastest rate among the rates in the present literature, which included ATC powders made by milling, , spray-drying, , cocrystallizing, , intensifying, coagglomerating, and so on. This result indicated that the crystal products prepared by bistream AC had the potential to produce the best medicines of ATC.…”
Section: Resultsmentioning
confidence: 55%
“…Additionally, these agglomerate particles still existed after 10 h, and it can be inferred that this part of ATC will not be absorbed by the body, thus causing the loss of the API. Surprisingly, this dissolution rate of the ATC crystals of the most uniform form I was also the fastest rate among the rates in the present literature, which included ATC powders made by milling, , spray-drying, , cocrystallizing, , intensifying, coagglomerating, and so on. This result indicated that the crystal products prepared by bistream AC had the potential to produce the best medicines of ATC.…”
Section: Resultsmentioning
confidence: 55%
“…HSP is used as an indicator of the miscibility between the component molecules to predict the likelihood of cocrystal formation. ,, In this model, the total force of various interactions can be divided into several partial solubility parameters, namely, dispersion (δ d ), polarity (δ p ), and hydrogen bonding (δ h ). , Each partial solubility parameter corresponds to the possibility of intermolecular interactions between molecules. Total solubility parameter (δ t ) is defined as The miscibility of compound molecules is estimated by various criterions, and all of them are based on the principle of “like dissolves like”.…”
Section: Methodsmentioning
confidence: 99%